Dele weds Destiny : [a novel] - Obaro, Tomi, 1990- (Alfred A. Knopf, 2022)
"A novel in which three Nigerian women, friends since their university days, are reunited in Lagos for the first time in thirty years at the lavish wedding of one of their daughters"--